Facilitating real-time cost collection and evaluating cost-effectiveness in a multi-armed study with government partners in Ghana. Issue 1 (2nd January 2023) - Hirji, Shahana; Park, Bethany; Tsinigo, Edward; Beg, Sabrin; Fitzpatrick, Anne; Lucas, Adrienne
ABSTRACT: Cost-effectiveness analysis (CEA) provides partners with information for allocating limited budget resources. Challenges in conducting CEAs include collecting data across multiple sources, introducing cost ssumptions, and delivering the results to partners. This paper introduces strategies to address these challenges using the example of the Strengthening Accountability to Reach All Students (STARS) project, a government-implemented differentiated instruction project in Ghana. To implement the programme for one school year, including opportunity costs related to training, the differentiated instruction plus basic management arm cost $48 per child, while the differentiated instruction plus basic and enhanced management training arm cost $84 per child.